2022
DOI: 10.7759/cureus.28704
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice Regarding Diabetes Mellitus Among Type 2 Diabetic Patients Attending Primary Health Care Centers in the Jazan Region of Saudi Arabia

Abstract: BackgroundDiabetes mellitus is a disease whose dramatic increase in prevalence worldwide poses a global health crisis. Saudi Arabia has the seventh highest rate of diabetes in the world and the second highest rate in the Middle East. The incidence of diabetes has risen due to insufficient knowledge, attitude, and practice surrounding the disease. Saudis' quality of life has decreased due to the recent rise in diabetes-related mortality and illnesses. Hence, leading healthy lives requires patients to have posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In our study, 88.23 % study population were found to have good knowledge. The KAP scores were slightly greater among males than females, which is similar to the study conducted by Mohammad A Mahzari et al (2022). …”
supporting
confidence: 88%
See 2 more Smart Citations
“…In our study, 88.23 % study population were found to have good knowledge. The KAP scores were slightly greater among males than females, which is similar to the study conducted by Mohammad A Mahzari et al (2022). …”
supporting
confidence: 88%
“…But 28 (33 %) had a poor glycaemic control. The level of practice of study subjects according to the KAP survey of T2DM conducted by Mohammad Uthman et al (2015) [9] was found to be low at 78 %, medium at 15%, and high at 7%. The highest practice score was found to be 29.…”
Section: Knowledge Of Study Subjects Towards Diabetes (Table 2)mentioning
confidence: 96%
See 1 more Smart Citation
“…The total score and its percentage for each participant were computed. Patients who scored below 50% were considered to have "insufficient knowledge" whereas those who scored 50% or more were considered to have "sufficient knowledge" [16,17].…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%
“…The Saudi people, in general, were aware of the dangers. Bani et al uncovered diabetes complexity variables in a large community-based study [30,31]. They enlisted 2,023 people from the general public and estimated their chance of developing diabetes.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%